Implementasi Business Intelligence Untuk Menganalisis Data Penyakit Diabetes Menggunakan Platform Tableau - Muhamad Saiful Arif; Kurniyati Nur; Ridwan Maulana Subekti; Reisa Inayah; Firman Noor Hasan (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2022)
Diabetes is a chronic metabolic disorder with multi-etiology characterized by high levels of sugar and is the result of insufficiency of insulin function present in the human body. The purpose of this article is to visualize and find out the rate of diabetes cases around the world based on the age range of the dataset that has been concentrated by implementing Business Intelligence to display confirmed case data, both in pregnancy, Body Mass Index (BMI), and blood pressure. The motto used is to process the world dataset from the www.kaggle.com data platform, this dataset is processed using the tableau desktop platform. The results of this article are in the form of reports in the form of Dashboards such as the number of confirmed cases both in pregnancy, Body Mass Index (BMI), and blood pressure that exist in the world and can be used to support a decision making. The interface display of the processed dataset is the result of an interestingly formed analysis, using an interactive Dashboard provided by tableau so that the data can be displayed attractively.